The political economy of violence against women - True, Jacqui (New York ; Oxford : Oxford University Press, 2012)
Violence against women is a major problem in all countries, affecting women in every socio-economic group and at every life stage. Yet, when women enjoy good social and economic status they are less vulnerable to violence across all societies. This book develops a political economy approach to understanding violence against women - from the household to the transnational level - accounting for its globally increasing scale and brutality.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Keywords: Women -- Violence against; Sex discrimination against women; Sex crimes; Women and war; Women -- Social conditions